2019
DOI: 10.1186/s12917-019-1932-7
|View full text |Cite
|
Sign up to set email alerts
|

A mini-pig model for evaluating the efficacy of autologous platelet patches on induced acute full thickness wound healing

Abstract: Background Autologous platelet concentrates are currently widely used across different areas of regenerative medicine in order to enhance the wound healing process. Although several protocols for platelet concentrates are available, their application remains difficult due to different protocols leading to distinct products with vary potential biological uses. In this study, we attempted to make a platelet patch (PP) using mixtures of platelet rich plasma (PRP) injection and platelet rich fibrin (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 48 publications
1
18
0
1
Order By: Relevance
“…Wound healing of the member of PRF group showed no signi cant difference from PRP treated animals but still lower in the healing percentage rate. Our results come in agreement with previous studies [36]. These reported that the liquid nature of the PRP increases the power of diffusion and invasion to the tissue, so the effect is faster than PRF which has a gel in nature.…”
Section: Discussionsupporting
confidence: 93%
“…Wound healing of the member of PRF group showed no signi cant difference from PRP treated animals but still lower in the healing percentage rate. Our results come in agreement with previous studies [36]. These reported that the liquid nature of the PRP increases the power of diffusion and invasion to the tissue, so the effect is faster than PRF which has a gel in nature.…”
Section: Discussionsupporting
confidence: 93%
“…PRP is a readily available and cost-effective therapy rich in growth factors and cytokines that enhances and supports tissue regeneration by stimulating cell migration and proliferation. Its application for the treatment of skin ulcers has already been widely reported both in humans (9,(22)(23)(24)(25) and animals (1,16,29,37,39,42). However, studies regarding the clinical efficacy of PRP in dogs for skin wound healing are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Positive results have been obtained also in the veterinary field, both in acute wound experimental models (26) or in the clinical practice to treat chronic non-healing wounds. In the literature, there are various reports on the use of PRP in veterinary medicine demonstrating that it might accelerate and stimulate the healing of acute wounds and promote the repair of impaired chronic wounds as observed in dogs (12,(27)(28)(29)(30)(31)(32), horses (1,16,(33)(34)(35)(36), cats (37,38), sheep (39), goat (40), and pigs (41,42). However, sometimes these results appear to be discordant, i.e., no positive effects of PRP are shown (2,43,44).…”
Section: Introductionmentioning
confidence: 99%
“…Applications of PRP in fracture repair had been shown in both dogs [49] and rabbit [48] by promoting bone healing. Interestingly, injection of PRP also promoted wound healing of soft tissue defects [50,51] as well as periodontal regeneration [52]. Since the present study did not evaluate the alteration of growth factors in PRP, it remains unknown whether the use of carprofen as a separation layer affecting the function of platelet-derived growth factors in PRP products.…”
Section: Discussionmentioning
confidence: 93%